The Analysis of Screening for Preeclampsia with the Maternal and Child Health Book - Indah Lestari; Noer Saudah; Naning Puji Suryantini; Hariyono; Budi Prasetyo (STIKes Patria Husada Blitar, 2026)
Preeclampsia is a complication that occurs during pregnancy, childbirth, and the postpartum period, characterized by hypertension, edema, and proteinuria. The government is trying various programs to reduce the incidence of pre-eclampsia. In addition to pre-eclampsia screening instruments, the results of documentation data in the Maternal and Child Health Book have many opportunities for analysis, to be used as indicators for early detection of pre-eclampsia. This study aimed to analyze the use of the maternal and child health book for early detection of Pre-Eclampsia. The research design was a correlational analysis with a cross-sectional approach. The sample was some pregnant women in Trimester II and III with research criteria, aged 20-35 years, primigravida and multigravida, gestational age ≥16 weeks, a total of 45 people, with a Purposive sampling technique. The independent variables were MAP (Mean Arterial Pressure), ROT (Roll Over Test), and BMI (Body Mass Index). The dependent variable was the incidence of Preeclampsia in pregnancy. The data Analysis used the Chi-Square test. The results obtained the greater the MAP and ROT value the greater the risk of preeclampsia, and obesity has a two times greater risk of preeclampsia. Increased MAP, ROT, and BMI indicate changes in the vascular system, disrupting the balance between vasodilator and vasoconstrictor factors, which can cause increased vascular resistance. which is a characteristic of preeclampsia. ROT and MAP measurements need to be carried out in each trimester so that early management can be carried out if pre-eclampsia occurs.